Preparing Special Education Personnel for Rural Schools: Current Practices and Future Directions - Barbara L. Ludlow (Journal of Research in Rural Education, 1998)
There has been dramatic growth in the number ofspecial education programs to serve students with special needs in the nation's schools since the federal mandate for a free appropriate public education in 1975. Such growth created a parallel demandfor qualified teachers and therapists to staffthese programs. This demand resulted in the development of a vast personnel preparation infrastructure to support the training, licensure, and employment ofpractitioners in special education and related services. The last two decades have witnessed a huge investment ofstate and federal funds into the development ofpreservice programs at colleges and universities; elaborate policies and procedures for state licensing and professional certification; and recruitment, retention, and staffdevelopment practices in local school systems. Rural schools have experienced major problems related to every aspect ofpersonnel preparation in special education: lack of preservice programs designed to prepare personnel for rural programs; an insufficient supply ofadequately trained and appropriately qualified personnel to staffrural positions; and significant difficulties in recruiting, retaining, and retraining teachers and therapists in rural areas. Despite ongoing experimentation and innovation in the area of preservice programs, licensure and certification policies, recruitment and retention efforts, and staff development activities, rural schools will continue to face these challenges as the next century begins. This article discusses current trends and future directions in personnel preparation in special education as they affect rural schools.